1996
DOI: 10.1083/jcb.134.4.849
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of human catalase to peroxisomes is dependent upon a novel COOH-terminal peroxisomal targeting sequence.

Abstract: Abstract. We have identified a novel peroxisomal targeting sequence (PTS) at the extreme COOH terminus of human catalase. The last four amino acids of this protein (-KANL) are necessary and sufficient to effect targeting to peroxisomes in both human fibroblasts and Saccharomyces cerevisiae, when appended to the COOH terminus of the reporter protein, chloramphenicol acetyl transferase. However, this PTS differs from the extensive family of COOH-terminal PTS tripeptides collectively termed PTS1 in two major aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
123
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 68 publications
7
123
0
1
Order By: Relevance
“…In contrast, catalase with C-terminal tetrapeptide KANL deleted was not detectable in any of the fractions (lanes 8 to 10). These results strongly suggested that catalase bound to Pex5p via C-terminal KANL, consistent with the report that KANL is the PTS of human catalase (32). Thus, a mode of recognition of catalase PTS by Pex5p resembled that of PTS1 but the import mechanisms of these cargoes were apparently distinguishable in the requirement for Pex5p-Pex13p interaction (Fig.…”
Section: Vol 22 2002 Peroxisome Targeting Signal 1 Receptor Pex5p 1645supporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, catalase with C-terminal tetrapeptide KANL deleted was not detectable in any of the fractions (lanes 8 to 10). These results strongly suggested that catalase bound to Pex5p via C-terminal KANL, consistent with the report that KANL is the PTS of human catalase (32). Thus, a mode of recognition of catalase PTS by Pex5p resembled that of PTS1 but the import mechanisms of these cargoes were apparently distinguishable in the requirement for Pex5p-Pex13p interaction (Fig.…”
Section: Vol 22 2002 Peroxisome Targeting Signal 1 Receptor Pex5p 1645supporting
confidence: 90%
“…PEX5 and PEX7 encode the receptors for PTS1 and PTS2, respectively. Of note, catalase with the Cterminal sequence KANL is also imported into peroxisomes by the Pex5p-dependent pathway (29,32). However, the underlying molecular mechanism for catalase import remains unclear.…”
mentioning
confidence: 99%
“…A range of C-terminal tripeptides have since been shown to function as PTS1s in various organisms in vivo (Gould et al, 1988;Aitchison et al, 1991;Purdue and Lazarow, 1996;Kragler et al, 1998). These generally fit the consensus sequence of , although a number of variants have been identified which only conform to this consensus in two out of three positions (Reumann et al, 2007).…”
Section: Pts1 (Peroxisomal Targeting Signal 1) Pathwaymentioning
confidence: 99%
“…Mammalian catalase has been shown to be targeted to the peroxisome by a four-amino-acid sequence of KANL at its C-terminus (Purdue and Lazarow, 1996). Alanine:glyoxylate aminotransferase is targeted by two signals (Huber et al, 2005); a C-terminal KKKL motif and an internal eightamino-acid sequence, both of which are predicted to be separately located on the surface of the protein (Ikeda et al, 2008).…”
Section: Pts1 (Peroxisomal Targeting Signal 1) Pathwaymentioning
confidence: 99%
“…Whereas in the case of the latter, amino acids in close proximity (i.e. within 10 -20 residues) to the C-terminal tripeptide can markedly influence the properties of, and allowable residues within, the PTS1 (16,17,(32)(33)(34)(35). The importance of specific residues near the C terminus appears to be particularly important if the C-terminal tripeptide deviates from the conservative consensus PTS1 (16).…”
mentioning
confidence: 99%